The personal-centered counseling approach foster student- learning independence - Ana Aprila; Luh Putu Sri Lestari; Kadek Suranata; Sefrianus Juhani (Indonesian Institute for Counseling, Education and Therapy (IICET), 2022)
One of the characteristics of the independent learning curriculum is student-centered learning. Students become a reference in finding patterns of learning and mentoring. In this context, teachers are required to seek power and efforts to foster the capability of students (student agency) in leading themselves. One pattern of assistance used by teachers, especially Counseling Guidance teachers is person-centered counseling. This research aims to determine the effectiveness of the Person-Centered counseling approach pattern in fostering student learning independence. The method used in this research is a systematic literature review. The stages in this method are planning, conducting, and reporting. The locus of this research is the literature research results of several researchers, who examined several schools related to the person-centered counseling approach. The results of this research are an increase in student independence in learning when the teacher applies a person-centered counseling pattern. This has been proven in several studies. On that basis, the application of the person-centered counseling approach model is something that is definitely needed to improve the quality of student learning.